Fertility options in Mayer-Rokitansky-Küster-Hauser syndrome - Francesco Fedele; Alessandro Bulfoni; Stefano Salvatore; Massimo Candiani (IMR Press, 2021)
Background: The Mayer-Rokitansky-Küster-Hauser (MRKH) syndrome is the most common cause of uterine aplasia, with a worldwide frequency of 1 in 4500 females. Although abundant literature is present regarding the different available methods for creating a neovagina in MRKH syndrome, the attention dedicated to these women's reproductive potential remains insufficient. Methods: Online searches were carried out in PubMed database during November and December 2020. The search included a combination of the various terms (e.g., MRKH, vaginoplasty, uterus transplantation, infertility treatment, gestational surrogacy, etc.). The following inclusion criteria were used: (1) The articles should be written in English or French language. (2) The article should have been published by an official scientific organization. Results: Until few years ago, the only option for women with MRKH syndrome was legal adoption, now gestational surrogacy (GS) and uterine transplantation (UTx) have become new fertility options available to these patients. Discussion: GS is officially recognized in several countries and widely practiced. On the other hand, UTx, although the great recent technical improvements, is far from being an option for all women with MRKH syndrome secondary to its complexity and the necessary immunologic therapies.